Optimization of the structure and properties of materials for dual purpose machines appointment : monograph - Hlushkova, D. B.; Volchuk, V. M. (NNI PDABA, 2024)
The monograph "Optimization of the structure and properties of materials for dual purpose machines" is devoted to solving the scientific problem of assessing the properties of dual-purpose metal materials based on the analysis of the spectrum of fractal dimensions of their structural components and improving the efficiency of friction pairs of parts of a volumetric hydraulic drive by choosing the material for their manufacture and its modes heat treatment. The scientifically proven effectiveness of using the ion-plasma method for coating the working surfaces of dual-purpose parts. Special software has been created that allows you to estimate the spectrum of statistical dimensions of heterogeneous structures with a complex geometric configuration of their elements. The results of theoretical and experimental research are implemented in production. The monograph is recommended for researchers, engineers, teachers of institutions of higher education, graduate students and students of institutions of higher education who specialize in the field of materials science and mechanical engineering.
Keywords: 669.017:519.21